Fertilisation with potato starch wastewater effect on the growth of Scots pine (Pinus sylvestris L.) forest in Poland - Nella Waszak; Filipe Campelo; Iain Robertson; Radosław Puchałka; Fatima-Zahraa El Balghiti; Jožica Gričar; Ali Boularbah; Marcin Koprowski (Trees, Forests and People, 2024)
Fertilisation is often used to increase plant productivity in agriculture but has also been used in forestry. In our study, Scots pine forest growing in a nitrogen-poor environment was fertilised with NPK post-production wastewater from a potato starch factory. Our research aimed to investigate the dependence of tree growth on different NPK concentrations. Cell characteristics such as cell wall thickness (CWT), lumen diameter (LD) and tree-ring features such as ring width (RW), total number of cells in annual growth (nTotal), earlywood (EW) and latewood (LW) were investigated. Twenty-six years of regular fertilisation of the forest with different doses of wastewater rich in NPK elements have affected the anatomical structure of Scots pine trees. It is presumed that the reduction in CWT and LD on the fertilised site was due to deficiencies in plant water conductivity, which may have occurred due to physiological drought. The influence of nitrogen on unfertilised site from the wastewater area could contribute to the CWT thickening. The results confirm that the use of NPK in excessive doses is detrimental to trees' conductive system.